Uncovering Drone Intentions using Control Physics Informed Machine Learning: data - Perrusquía, Adolfo; Wei, Zhuangkun; Guo, Weisi; Fraser, Benjamin (Cranfield University, 2024)
This repository provides the data and code of the paper "Uncovering Drone Intentions using Control Physics Informed Machine Learning"
Keywords: drone intentions'; 'physics informed'; 'reward function'; 'deep learning'; 'machine learning'